Dynamics of Poverty in the Philippines: Distinguishing the Chronic from the Transient Poor - Aubrey D. Tabuga; Christian D. Mina; Celia M. Reyes; Ronina D. Asis; Maria Blesila G. Datu (Philippine Institute for Development Studies (PIDS), 2011)
Poverty incidence among population rose from 24.9 percent in 2003 to 26.4 percent in 2006 and then inched up further to 26.5 percent in 2009. Although this aggregate poverty rate shows only a few percentage points change from 2003 to 2009, this does not mean there are no movements in and out of poverty. Based on a matched panel data obtained from three survey years of the Family Income and Expenditure Survey, this paper aims to look into the dynamics of poverty. The main objective is to draw a line between the chronic and transient poor, and to determine the factors that have made people exit poverty and those that dragged many nonpoor households into poverty.
Keywords: 330; Philippines; panel data; poverty analysis; chronic and transient poverty; dynamics of poverty; Armut; Soziale Mobilität; Philippinen